Modification of Extraction Methods on Determining Simeticone Suspension Using FTIR Method - Ida Musfiroh; Aliya Nur Hasanah; Gia A. Faradiba; Ida Ayumiati; Mutakin Mutakin; Muchtaridi Muchtaridi (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Antacids dosage form are a class of drugs used to chemically bind and neutralize stomach acid. Simethicone is one of the antacids that works as an antiflatulant. In an effort to guarantee the quality of a preparation, a valid analysis method is needed that meets the validation parameters. This study aims to modified of extraction method of the simethicone content of suspension samples using the FTIR method. The methods include simethicone modification of extraction from suspension preparations with toluene solvents and hydrochloric acid (2:5) 3.35. Validation methods include: determination of precision, accuracy, limit of detection (LOD), and limit of quantification (LOQ) at wave number 1261 cm-1 and determination of the content of samples of simethicone suspension. The results showed that linearity parameters with a correlation coefficient of 0.997 in a concentration range of 1000-10,000 ppm, precision with a value of KV <2%, LOD and LOQ, respectively 378.97 and 1250.59 ppm. The results of the determination of simethicone suspension samples indicate that this method met the requirements of the validation parameters.Keywords: Validation, Simethicone, Infrared Spectrophotometry, antacid